Pinning Down the Transcription: A Role for Peptidyl-Prolyl cis-trans Isomerase Pin1 in Gene Expression - Hu, Xiangming; Chen, Lin-Feng (Frontiers in Cell and Developmental Biology, 2020)
Pin1 is a peptidyl-prolyl cis-trans isomerase that specifically binds to a phosphorylated serine or threonine residue preceding a proline (pSer/Thr-Pro) motif and catalyzes the cis-trans isomerization of proline imidic peptide bond, resulting in conformational change of its substrates. Pin1 regulates many biological processes and is also involved in the development of human diseases, like cancer and neurological diseases. Many Pin1 substrates are transcription factors and transcription regulators, including RNA polymerase II (RNAPII) and factors associated with transcription initiation, elongation, termination and post-transcription mRNA decay. By changing the stability, subcellular localization, protein-protein or protein-DNA/RNA interactions of these transcription related proteins, Pin1 modulates the transcription of many genes related to cell proliferation, differentiation, apoptosis and immune response. Here, we will discuss how Pin regulates the properties of these transcription relevant factors for effective gene expression and how Pin1-mediated transcription contributes to the diverse pathophysiological functions of Pin1.